Intranasal Ectopic Tooth- A Rare Case Report - Koirala, Krishna Prasad; Karki, Bikram Babu; Maharjan, Manita (Journal of College of Medical Sciences-Nepal, 2020)
Presence of ectopic tooth in the nasal cavity of an adult is a rare phenomenon. Exact etiology of this condition is yet to be confirmed. We report a case of a 40-year-old woman, who presented to us with the history of left nasal obstruction of one-year duration along with pain in the left side of face revealing an on examination. Intranasal tooth was removed by surgical intervention with Luc’s forceps. The patient’s nasal obstruction and facial pain subsided after the treatment. We need to suspect an intranasal tooth when there is a white substance mimicking bone in the nasal cavity in patients presenting to us with facial pain and nasal obstruction Keywords: intranasal tooth; nasal obstruction; surgical extraction